Effect of Chronic Morphine Consumption on Synaptic Plasticity of Rat’s Hippocampus: A Transmission Electron Microscopy Study - Mohammad Hassan Heidari; Abdollah Amini; Zohreh Bahrami; Ali Shahriari; Abolfazle Movafag; Reihane Heidari (Neurology Research International)
It is well known that the synapses undergo some changes in the brain during the course of normal life and under certain pathological or experimental circumstances. One of the main goals of numerous researchers has been to find the reasons for these structural changes. In the present study, we investigated the effects of chronic morphine consumption on synaptic plasticity, postsynaptic density thickness, and synaptic curvatures of hippocampus CA1 area of rats. So for reaching these goals, 24 N-Mary male rats were randomly divided into three groups, morphine (n=8), placebo (n=8), and control (n=8) groups. In the morphine group, complex of morphine (0.1, 0.2, 0.3, and 0.4) mg/mL and in the placebo (sucrose) group complex of sucrose (% 0.3) were used for 21 days. After the end of drug treatment the animals were scarified and perfused intracardinally and finally the CA1 hippocampal samples were taken for ultrastructural studies, and then the obtained data were analyzed by SPSS and one-way analysis of variance. Our data indicated that synaptic numbers per nm3 change significantly in morphine group compared to the other two groups (placebo and control) (P<0.001) and also statistical analysis revealed a significant difference between groups in terms of thickness of postsynaptic density (P<0.001) and synaptic curvature (P<0.007). It seems that morphine dependence in rats plays a main role in the ultrastructural changes of hippocampus.